Performance pay and the gender wage gap: Evidence from Spain - Sara de la Rica; Juan José Dolado; Raquel Vegas (Institute for the Study of Labor (IZA), 2010)
This paper uses detailed information from a large wage survey in 2006 to analyze the gender wage gap in the performance-pay (PP) component of total hourly wages and its contribution to the overall gender gap in Spain. Under the assumption that PP is determined in a more competitive fashion than the other wage components, one would expect, in principle, to find a low gender gap in PP. However, this is not what we find. After controlling for observable differences in individual and job characteristics as well as for non random selection, the adjusted gender gap in PP reaches 26 log points, displaying a glass ceiling pattern. After examining several alternative theories that could rationalize these findings, we conjecture that monopsonistic features, possibly related to women's lower labour mobility due to housework, fit better with our results than other theories related to occupational segregation.
Keywords: J31; J33; J42; J71; 330; Performance pay; gender gaps; selection bias; quantile regressions; Lohndifferenzierung; Frauenarbeitslohn; Leistungsorientierte Vergütung; Weibliche Arbeitskräfte; Arbeitsmobilität; Hausarbeit; Schätzung; Spanien